Corporate governance mechanisms and environmental reporting of nigerian oil & gas companies - John Ayoor Ivungu; Amos I. Ganyam; Tarsue Asema; AustineUjah Ogirah (Journal of Management and Science, 2021)
This paper examined whether corporate governance mechanisms (CGM) affectenvironmental reporting (ER) of Nigerian oil & gas companies. The ex-post facto design was used and data were acquired from eight (8) oil & gas companiesthat are quotedon the Nigerian exchange group from 2011 to 2020. CGM was measured in Board Size (BS), Board Independence (BI), and Board Ownership (BO) while Environmental Reporting Index was used as a measure for ER. Panel regression technique and specifically random effects were used for data analysis. Findings suggested that BS decrease ER significantly while BI and BO significantly increase ER. The study concluded that the CGM of Nigerian oil & gas companiesaffects environmental reporting significantly. The recommendation was that companies who want to improve their level of environmental reporting to enjoy the benefits that come with doing so should pay closer attention to CGM (board size, independence, and ownership).